The Ulama in Aceh: A Brief Historical Survey - Saby, Yusny (Studia Islamika, 2001)
This article is a survey primarily concerned with the social and political roles of some leading ulama in Aceh, one of the most important areas for the development of Islam in the Malay-Indonesian Archipelago. As the work of Azyumardi Azra argued, Aceh emerged as the leading center of Islamic learning in the seventeenth and eighteenth centuries Malay-Indonesia; The leading ulama originated from Aceh and Islamic thought mainly developed there. Hamzah al-Fansûrî and Nur al-Din al-Raniri-to mention but a few-were among the Acehnese ulama who contributed to the Islamic intellectual development during the periode concerned. They were responsible for the spread of, respectively, heterodox sufisme wahdat al-wujûd and neosufisme in Malay-Indonesian Islam.DOI: 10.15408/sdi.v8i1.694